A Case of Rapidly Progressing Frontotemporal Dementia - Purkayastha, Debasweta (Indian J Psychol Med, 2018)
Frontotemporal dementia commonly presents as a gradual change in personality, social conduct, and language ability, often sparing memory loss in early stages. We report a case of a 55-year-old female with rapid progression of memory impairment and other cognitive functions in a span of 2 years.